Morocco : Selected Issues. (IMF Staff Country Reports; Country Report, 2018)
This Selected Issues paper examines the distributional effects of tax reforms in Morocco. Overall, the performance of Morocco's tax system is satisfactory, but there is scope to strengthen it and make it more equitable and less distortive. Morocco would benefit from a comprehensive and well explained tax reform strategy aiming to reduce inequality and boost growth. For this, a recommended tax reform package should combine several key components, for example, reducing tax exemptions, raising property tax, and lowering corporate tax rates. At the same time, the targeting of social programs should be strengthened. Such a reform approach would protect the most vulnerable and help broaden the tax base, remove tax distortions, and better share the tax burden.